A simple approach for obtaining unsaturated hydraulic conductivity based on the soil water content - Marcos de Sousa Campos; Eugênio Ferreira Coelho; Francisco Airdesson Lima do Nascimento; Marcelo Rocha dos Santos; Lucas Melo Vellame; Luiz Antonio Conceição de Carvalho; José Carlos Lopes de Lima; Damiana Lima Barros (Acta Scientiarum. Agronomy, 2026)
Knowledge of soil hydraulic conductivity is indispensable due to its application in studies of soil water dynamics, water balance, and irrigation management in crops that directly affect water and soil conservation. The objective of this study was to propose two alternatives for determining unsaturated hydraulic conductivity using existing methodologies in the literature based on the variation in soil moisture and water storage monitored using a moisture sensor in a drainage lysimeter and under field conditions. Two experiments were conducted, one in a drainage lysimeter and the other in the field at Embrapa Cassava and Fruit Farming, Cruz das Almas, Bahia State, Brazil. A comparison of moisture and storage variation between the proposed methodologies was carried out based on statistical coefficients. The methods based on moisture and storage variation in a layer estimated the unsaturated hydraulic conductivity with good accuracy compared to Hillel’s method. Hydraulic conductivity showed greater variation in the initial phase of water redistribution in the soil, either in the lysimeter test or in the field application after irrigation. The proposed methods based on moisture and storage variation can be applied to studies on soil water dynamics in the soil moisture profile using soil water sensors.